2018
DOI: 10.4102/sajce.v8i1.513
|View full text |Cite
|
Sign up to set email alerts
|

Using structured movement educational activities to teach mathematics and language concepts to preschoolers

Abstract: Methods: A qualitative exploratory case study design was used to explore the extent to which structured movement educational assessment activities can support the understanding of mathematics and language concepts. The participants included 20 Grade R learners, one class teacher and one head of department (HOD). The data were generated using observation of participants, analysis of worksheets, visual data and a semi-structured interview. Results:The findings of the study suggest that the integration of structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…This result coincides with the study results of ) Ford, 2016( and)Omidire, et al, 2018) in the positive effect of using movement-based learning in improving the mathematical achievement.…”
Section: Study Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result coincides with the study results of ) Ford, 2016( and)Omidire, et al, 2018) in the positive effect of using movement-based learning in improving the mathematical achievement.…”
Section: Study Results and Discussionsupporting
confidence: 91%
“…This result coincides partially with the study results of: )Nadler et al, 2015( in students' concentration, enjoyment of learning, engagement in learning, ) Riley et al, 2017( in the positive effect on children's enjoyment and engagement, and ) Omidire et al, 2018( in the positive impact on learners' physical and social development.…”
Section: Study Results and Discussionsupporting
confidence: 91%
“…The studies included in this review were published between 2018 and 2021, as seen in Figure 3. In 2018, a total of n=3 articles (Hinkley et al 2018, McCree et al 2018, Omidire et al 2018 were found to have researched outdoor play among children. In addition, there were n=4 studies identified from 2019 (Gil-Madrona et al 2019, Omidvar et al 2019, Sando 2019, Wainwright et al 2019) and 2021 (Almers et al 2021, Fathirezaie et al 2021, Mygind et al 2021, Riazi et al 2021, respectively, from the three databases.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of distribution, the highest number of studies were conducted in the United Kingdom (McCree et al 2018, Wainwright et al 2019, Australia (Hinkley et al 2018, Mygind et al 2021 and Canada (Omidvar et al 2019, Riazi et al 2021) with n=2 articles, respectively. Other countries that were also included in these studies were Turkey (Bay 2020), South Africa (Omidire et al 2018), the United States (Rymanowicz et al 2020), Spain (Gil-Madrona et al 2019, Norway (Sando 2019), Iran (Fathirezaie et al 2021), and Sweden (Almers et al 2021), with n=1 articles each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation